Development of a Predictive Nomogram for the Change in PT/INR Upon Discontinuation of Bivalirudin as a Bridge to Warfarin. (July 2017) - Hohlfelder, Benjamin; DeiCicchi, David; Sylvester, Katelyn W.; Connors, Jean M.
Appropriate timing of bivalirudin discontinuation as a bridge to warfarin is complicated, as bivalirudin may cause a falsely prolonged international normalized ratio (INR). The purpose was to evaluate patient and medication characteristics associated with differences in INR prolongation caused by bivalirudin. Adult patients receiving bivalirudin as a bridge to warfarin in 2014 were retrospectively evaluated. Patients were excluded if they had known thrombophilia or inappropriate INR monitoring after discontinuation of bivalirudin. Data recorded included indication for bivalirudin use, bivalirudin dosing, and coagulation assays. Univariate analysis was performed to determine variables associated with a larger change in INR when discontinuing bivalirudin. Variables with P < .3 were included in multivariate analysis. In total, 50 patient admissions were included in the analysis. Patients with ventricular assist devices represented the majority of the patient population (74%). The most common INR goals were 2.0 to 3.0 and 2.5 to 3.5. The mean initial weight-based bivalirudin rate was 0.076 mg/kg/h, and the mean increase in INR when starting bivalirudin was 0.6. The mean final weight-based bivalirudin rate was 0.13 mg/kg/h, and the mean change in INR after stopping bivalirudin was 0.8. On multivariate analysis, factors associated with a larger change in INR after stopping bivalirudin included higher serum creatinine ( P = .033), greater change in INR after initiation of bivalirudin ( P = .028), and higher final bivalirudin rate ( P < .001). The change in INR when starting or stopping bivalirudin appears to be patient specific and dose related. A nomogram was developed to predict the ideal timing of bivalirudin discontinuation. Prospective evaluation of the nomogram is under way.